Knowledge and practice of dental professionals regarding vertical teeth preparation techniques - Nasser M. Alahmari; Mohammed A. K. Al-Haboob; Thrya S. Gadah; Nassreen H. Albar; Mohammed M. Al Moaleem; Mohammed E. Sayed; Ashraf Mohammed Alhumaidi; Taha M. A. S. Al-Amri; Shehab S. A. Diaban; Abdulrahman A. H. S. Tajedin (BMC Medical Education)
Abstract Background Vertical preparation techniques (VPTs), particularly the biologically oriented preparation technique (BOPT), have gained prominence in restorative dentistry due to their conservative approach to tooth structure preservation and improved aesthetic outcomes. This study aims to assess the knowledge and clinical practices of VPTs, including BOPT, among dental professionals in Sanaa, Yemen, and explore the barriers to their widespread use. Materials and methods An online cross-sectional survey was conducted among general practitioners and specialists in Sanaa, Yemen using a structured, self-administered questionnaire. The survey explored the participants’ knowledge, familiarity, and clinical use of VPTs and their perceptions of its advantages and challenges. Data were analyzed using descriptive statistics and Chi-square tests to evaluate associations between professional roles and VPT knowledge and practice. P values < 0.05 indicated statistical significance. Results Out of 285 participants, 76.8% were familiar with VPTs but only 11.6% reported using these approaches in clinical practice. The primary source of knowledge acquisition was informal, with 26.3% of the participants citing social media as their main resource. Specialists demonstrated significantly higher proficiency and confidence in applying VPTs compared with general practitioners (p < 0.05). Key challenges identified in clinical adoption were controlling gingival bleeding (32.28%) and achieving precise margins during tooth preparation (34.74%). The majority (55.8%) of participants acknowledged the potential of VPTs as the future of restorative dentistry. Despite these benefits, 36.1% of the respondents emphasized the need for further training and educational programs to enhance proficiency and overcome the perceived complexity of these techniques. Conclusion This study highlights significant gaps in the knowledge and practice of VPTs, particularly BOPT, among the participants. While these techniques offer promising clinical and aesthetic benefits, their adoption is hindered by inadequate training and perceived complexity. Targeted educational interventions and further research are needed to support the broad implementation of VPTs in clinical practice. Clinical trial number Not applicable.